1994
DOI: 10.3168/jds.s0022-0302(94)77220-9
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Delivery of Nutrients for Milk Protein Synthesis by Portal-Drained Viscera

Abstract: The predictability of diet effects on milk composition is limited by the lack of understanding of the metabolic transformations that absorbed nutrients undergo within the portal-drained viscera and liver of high yielding dairy cows. The mass of splanchnic tissues increases dramatically in early lactation, but little is known about the regulation of gut growth and adaptation in early lactation, and further research may provide strategies for optimizing gut adaptation. Glucose is critical for milk synthesis, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0
6

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 131 publications
4
81
0
6
Order By: Relevance
“…Our results indicate that there was a higher use of AA for glucose production leading to a higher milk lactose yield on the AB treatment than on the AP treatment. This agrees with the lower plasma concentrations of Ala, which is perhaps the most important glucogenic AA (Reynolds et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Our results indicate that there was a higher use of AA for glucose production leading to a higher milk lactose yield on the AB treatment than on the AP treatment. This agrees with the lower plasma concentrations of Ala, which is perhaps the most important glucogenic AA (Reynolds et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the present experiment was designed to compare increased AA and glucose supplementation to cows in negative energy balance. The infusion periods lasted for 6 days and thus the duration should be suitable for achieving milk production responses since infusion responses largely occur within 1 to 3 days (Metcalf et al, 1996;Reynolds et al, 1994). Moreover, Knowlton et al (1998) showed by summarising literature data that short-term (,1 week) infusion of glucose increased milk yield, whereas longer infusion indicated no prolonged responses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations